Pengaruh Model Inkuiri Terhadap Hasil Belajar Siswa Kelas IV SD Negeri 122365 Pematang Siantar - Rico Ary Gunawan Silaban; Andriono Manalu; Esti Sirait (JOURNAL SAINS STUDENT RESEARCH, 2023)
This research aims to determine the influence of the inquiry model on the learning outcomes of class IV students with chapter 3 styles around us at state elementary school 122365 Pematang Siantar odd semester FY 2023/2024. The type of research in this research is quantitative research. The research population was all students in class IV A and IV B at SD Negeri 122365 Pematang Siantar totaling 50 students. The sampling technique in this research isnonequivalent control group design, where sampling is saturated. Saturated sampling is a sampling technique where members of the population are used as samples. The sample in this study consisted of class IV A of SD Negeri 122365 Pematang Siantar, totaling 25 students. The results of this study show that the average value is 38.80 and the learning outcomes value is based on an average score of 80.7. The results of the t distribution test at the significance level (ɑ = 0.05), dk = N-1 = 50-1 = 49, namely tcount>ttable, so the data has a tcount distribution of 71.607. It can be said that there is a significant influence. The results of the t-test table prove that there is an influence of the inquiry model (X) on learning outcomes (Y) with the t-count results. The t-test results are 71.607, while tcount= 2,009. Face tcount> ttablenamely 71.607 > 2.009. This proves that there is a significant influence of the inquiry model on the learning outcomes of class IV in chapter 3 styles around us at state elementary school 122365 Pematang Siantar.